Dilated Cardiomyopathy Post COVID-19 Infection in Children: Case Report - Heykel Madjido, Donny; Febrina Tambunan, Tiur (Jurnal KESANS : Kesehatan dan Sains, 2024)
Introduction: Dilated cardiomyopathy (DCM) is a disorder of cardiac muscle characterized with ventricular dilatation and decreased diastolic function. Although the most common cause of DCM is idiopathic, several cases of DCM in COVID-19 infection have been reported. Case report: A 2 years-old boy presented with shortness of breath and cough for 2 weeks, especially during activity. Physical examination revealed hypertension, tachypnoea, fever, crackles in both lungs, and intracoastal retractions. Chest x-ray showed cardiomegaly (CTR 0.63) and minimal pulmonary enema as well as inhomogeneous perihilar and right paracardial opacity with ill-defined borders and air bronchogram. SARS-CoV-2 IgG was positive. Echocardiography confirmed DCM, pulmonary hypertension, and minimal pericardial effusion. Discussion: Echocardiographic for ventricular dysfunction is considered the best method for evaluation and diagnosis. Treatment for DCM depends on the degree of myocardial remodelling and the clinical symptoms. The latest management algorithm recommends the use of ACE-Inhibitors, B-Blockers, and Diuretics. The patient experienced improvement after 2 weeks of treatment with furosemide, captopril, spironolactone, and digoxin therapy. Conclusion: Diagnosis and management of DCM depends on the clinical findings and imaging, and requires subspecialty management. Since the COVID-19 pandemic, it is necessary to consider COVID-19 infection in children with symptoms of respiratory tract infection